Identification of a rare copy number polymorphic gain at 3q12.2 with candidate genes for familial endometriosis - Flávia Gaona Oliveira; Júlio Cesar Rosa-; Alexandra Galvão Gomes; Juliana Dourado Grzesiuk; Thiago Vidotto; Jeremy Andrew Squire; Rodrigo Alexandre Panepucci; Juliana Meola; Lúcia Martelli (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Endometriosis is a complex disease that affects 10-15% of women of reproductive age. Familial studies show that relatives of affected patients have a higher risk of developing the disease, implicating a genetic role for this disorder. Little is known about the impact of germline genomic copy number variant (CNV) polymorphisms on the heredity of the disease. In this study, we describe a rare CNV identified in two sisters with familial endometriosis, which contain genes that may increase the susceptibility and progression of this disease. We investigated the presence of CNVs from the endometrium and blood of the sisters with endometriosis and normal endometrium of five women as controls without the disease using array-CGH through the Agilent 2x400K platform. We excluded common CNVs that were present in the database of genomic variation. We identified, in both sisters, a rare CNV gain affecting 113kb at band 3q12.2 involving two candidate genes: ADGRG7 and TFG. The CNV gain was validated by qPCR. ADGRG7 is located at 3q12.2 and encodes a G protein-coupled receptor influencing the NF-kappaβ pathway. TFG participates in chromosomal translocations associated with hematologic tumor and soft tissue sarcomas, and is also involved in the NF-kappa B pathway. The CNV gain in this family provides a new candidate genetic marker for future familial endometriosis studies. Additional longitudinal studies of affected families must confirm any associations between this rare CNV gain and genes involved in the NF-kappaβ pathway in predisposition to endometriosis.